Identification: a romance in redemption - Kenyon, Essek William (Whitaker House, 2021)
"Using passages from the New Testament, discusses the legal side of redemption whereby Christians may identify with Jesus by continuing the work he did during his life on earth, joining in his humanity on the cross, and realizing kinship with him and his Father in heaven"--